小脳橋角部周辺頭蓋底腫瘍への6つのアプローチ - 中冨 浩文; 宮崎 日出海 (JIBI INKOKA TEMBO, 2009)
We propose the complete understanding and learning of 6 basic skull base approaches to the cerebellopontine angle lesions. By mastering these 6 approaches, we have only to combine several approaches altogether for treating any lesions around the cerebellopontine angle. Three illustrative cases are presented here who achieved gross total removal in two and subtotal removal in one by combining several skull base approaches.Also we introduce our utilization of the continuous neurophysiological monitoring to optimize the functional preservation. Several electrophysiological recordings are presented in this report. 小脳橋角部周辺の頭蓋底病変は, その病変の主座と隣接する脳神経の種類から, 傍三叉神経領域, 傍聴神経 (蝸牛神経) 領域, 傍嚥下神経領域の3つに分類できる。これらの3領域にそれぞれ最も適切な頭蓋底手術アプローチが2つずつあり, これらの6つの基本アプローチを組み合わせることで, すべての小脳橋角部周辺の頭蓋底外科手術のための術野が得られる。脳幹と頭蓋底を結ぶ脳神経は, 過度のストレス損傷を一定時間に一定以上受けると再生しない。我々は神経機能を最大限に維持するために, 術中に持続神経機能モニタリングを併用した神経機能温存手術をチームアプローチによって行っている。安全で確実なアプローチと, 信頼度の高い術中モニタリングを使用することにより, これまでの小脳橋角部周辺の頭蓋底手術において, 恒久的な脳神経麻痺, 手足の麻痺はほとんど経験していない。